2011
DOI: 10.1111/j.1440-1746.2010.06329.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective validation of the Chinese University Prognostic Index and comparison with other staging systems for hepatocellular carcinoma in an Asian population

Abstract: We have validated CUPI in a population composed of predominant HBV-related HCC. CUPI is an appropriate staging system for HBV-related HCC. In patients with advanced HCC, both CUPI and CLIP offer good risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 44 publications
5
56
1
Order By: Relevance
“…Patients who had stage III and stage IV disease also were grouped for evaluation because of the similar outcomes in this group, as demonstrated in a previous study. 13 Within both groups of patients (stages I/II and stages III/IV), the IL-10 level further stratified patients into 2 categories with statistically significant, distinct overall survival (P ¼ .0066 and P ¼ .0002, respectively).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who had stage III and stage IV disease also were grouped for evaluation because of the similar outcomes in this group, as demonstrated in a previous study. 13 Within both groups of patients (stages I/II and stages III/IV), the IL-10 level further stratified patients into 2 categories with statistically significant, distinct overall survival (P ¼ .0066 and P ¼ .0002, respectively).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…13 To examine the robustness of the prognostic significance of serum IL-10 and to minimize the problem of hypercollinearity, 2 multivariate analyses with different sets of data were conducted. For the first multivariate analysis, the following factors were included: sociodemographics (age, sex, ECOG performance status), log IL-10, tumor staging (BCLC, CLIP, TNM, Okuda, CUPI), treatment modality (locoablative therapy vs palliative therapy), Child-Pugh stage, ALT level, and MELD score.…”
Section: Study Variables and Tumor Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various staging systems used in HCC include the European systems [French staging system, 6 Barcelona Clinic Liver Cancer (BCLC) staging system 7 and the cancer of the liver Italian program (CLIP) 8 ], Asian systems [Okuda staging system, 9 Japan integrated Staging (JIS), 10 Tokyo score 10 and Chinese University Prognostic Index (CUPI) 11 ].…”
Section: Staging Systems In Hepatocellular Carcinomamentioning
confidence: 99%
“…CUPI performed the best in predicting 3-month survival while CLIP performed better in predicting the outcome of 6-and 12-month survival rate. 11 A study from Japan involving 1173 HCC patients found that the bm-JIS score showed good stratification ability and was demonstrated to be a better predictor of the prognosis than the c-JIS score and the BALAD score, especially for the patients with a good prognosis. 13 In a recent study 15 comparing CLIP staging with Okuda staging system and Child-Pugh scoring system, CLIP staging was found to give more accurate prognostic information in comparison to Okuda and Child-Pugh classification.…”
Section: Choosing the Staging Systemmentioning
confidence: 99%